Potensi Ekowisata Mangrove Muara Baimbai dalam Meningkatkan Pendapatan Masyarakat Desa Sei Nagalawan Kabupaten Serdang Bedagai - Hafni, Roswita; Elvira Sandi, Distia (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2025)
The mangrove forest rehabilitation program by the Ministry of Environment and Forestry can support ecosystem recovery and increase community income through mangrove tree planting, conservation area management, as well as mangrove-based training and education. The development of mangrove-based ecotourism can be a key driver in boosting the economic growth of coastal areas. The Mangrove Ecotourism of the Muara Baimbai Forest Farmers Group in Sei Nagalawan Village not only has great potential to be developed, but also plays an important role as an alternative source of income for the local community. This study aims to analyze the contribution of Muara Baimbai mangrove ecotourism to the income of the community, with the majority of residents depending on the marine capture fisheries sector. Data were collected through in-depth interviews with 30 families and members of the Forest Farmers Group (KTH) as the main managers of the ecotourism, participatory observation, questionnaires, documentation, and focused group discussions (FGD). The results of the study show that the presence of ecotourism has a positive economic impact on the community, creates new job opportunities, and promotes the development of local ingredient-based culinary products. Local natural tourism products include mackerel fish crackers and jeruju chips, which are made directly by the Sejati Women’s Group. This delicacy has a distinctive flavor and has become one of the favorite souvenirs for tourists. This ecotourism also promotes environmental conservation awareness, particularly the planting and protection of mangrove forests. The role of the Forest Farmers Group (KTH) is very significant in managing, developing, and involving the local community in sustainable tourism activities. This study recommends strengthening the institutional capacity of the Forest Farmers Group and promoting ecotourism more broadly to improve the welfare of the village community.